Food waste - Policies, initiatives and consumer behaviour. Case study: Poland and Portugal - Papaj, Katarzyna Anna (2017)
Food waste is a serious ethical, environmental and economic problem of excessive contemporary consumerism. The European Union (EU) estimates that around 88 million tonnes of food are wasted annually, with associated costs estimated at 143 billion euros. Food waste occurs in all phases of the food supply chain, starting with producers and ending with consumers, and this food waste has a staggering environmental impact. There are several factors which contribute to excessive quantities of wasted food. Some are related to current production systems and product commercialization, including food quality and security norms, others are more personal like people’s food habits, awareness, values and consumer attitudes in regards to consumption and food waste. In order to implement policies, strategies and measures which contribute to reducing food waste on the consumer level there is a need to understand the factors which shape consumer behaviours. Starting with the models and variables indicated in the literature overview, possible determinants of environmental behaviour were presented. Through these variables the study seeks to estimate if there is a differences between consumers in countries with different contexts and food habits by choosing Poland and Portugal as the case studies. The main differences between these countries lies in two key aspects which could have an influence not only on the behaviour related to consumption and wasting food but also on self-awareness and attitudes towards the problem. On the one hand Poland is one of the most agricultural country in the EU, while Portugal has already lost much of its agricultural production, whilst on the other hand, Polish and Portuguese food habits are different. To achieve these objectives in terms of methodology, an online survey was created. The survey was translated into Polish and Portuguese and its goal was to understand the reasons for food waste, purchasing behaviour, attitudes, the level of consumer knowledge and opinions with respect to food waste, as well as perception about the quantities of wasted food in the consumer’s household. Based on responses obtained in the survey in which 232 Polish and 244 Portuguese consumers participated, the conclusion is that despite the different contexts and food habits some of the behaviours and opinions are similar, namely the motives for throwing food away and opinions about the measures which could be taken to reduce food waste. Through the analysis, the results have shown that Polish consumers waste more than Portuguese and have less positive attitudes towards food waste than Portuguese consumers. Furthermore, the Polish seem to attribute less importance to the food waste problem and have less knowledge about food waste. These differences could be not only due to different contexts and food habits but also to the types of campaigns and initiatives which Governments and Governmental organizations from both countries have implemented.